(untitled) (Journal of Comparative & International Higher Education, 2022)
The global COVID-19 pandemic has significantly affected many areas of life including higher education. Educational practices were disrupted, and higher education institutions had to move from in-person to remote teaching quickly to continue education. This transition brought along challenges not only for students but also for faculty. Currently there is limited research on faculty teaching experiences during the pandemic. Using the photovoice method, we explored the experiences of higher education faculty in two Turkish universities when teaching remotely during the pandemic. We identified three areas that were important and influenced faculty member practices: Faculty well-being, lack of preparation, and wrestling with remote education. Our findings grounded in faculty experiences provide insights and areas for higher education institutions to improve remote education practices and provide support to foster student learning, particularly if institutions decide to continue with online education permanently or offer hybrid education options.